Mind the gap: The interplay between external and internal actions in the case of corporate social responsibility - Hawn, Olga; Ioannou, Ioannis (Strategic Management Journal, 2016)
Research summary : We explore the effect of the interplay between a firm's external and internal actions on market value in the context of corporate social responsibility ( CSR ). Specifically, drawing from the neo‐institutional theory, we distinguish between external and internal CSR actions and argue that they jointly contribute to the accumulation of intangible firm resources and are therefore associated with better market value. Importantly, though, we find that, on average, firms undertake more internal than external CSR actions, and we theorize that a wider gap between external and internal actions is negatively associated with market value. We confirm our hypotheses empirically, using the market‐value equation and a sample comprising 1,492 firms in 33 countries from 2002 to 2008. Finally, we discuss implications for future research and practice . Managerial summary : Companies often accumulate intangible assets by taking internally and externally oriented CSR actions. Contrary to popular beliefs, the data show that they undertake more internal than external ones: firms do more and communicate less. How does a potential gap (i.e., a misalignment) between internal and external CSR actions affect a firm's market value? We find that although together (the sum of) internal and external actions are positively associated with market value, a wider gap has negative implications. In other words, firms do not realize the full benefits of their internal actions when such actions are not externally communicated to key stakeholders, and to the investment community in particular. This negative association with market value is particularly salient in CSR ‐intensive and the natural resources and extractives industries . Copyright © 2015 John Wiley & Sons, Ltd.